2012
DOI: 10.1371/journal.pone.0034422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tp53 Codon 72 Polymorphisms, Tp53 Mutations, and HPV Infection in Cutaneous Squamous Cell Carcinomas

Abstract: BackgroundNon-melanoma skin cancers are one of the most common human malignancies accounting for 2–3% of tumors in the US and represent a significant health burden. Epidemiology studies have implicated Tp53 mutations triggered by UV exposure, and human papilloma virus (HPV) infection to be significant causes of non-melanoma skin cancer. However, the relationship between Tp53 and cutaneous HPV infection is not well understood in skin cancers. In this study we assessed the association of HPV infection and Tp53 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 98 publications
1
12
0
Order By: Relevance
“…A dimorphism of the TP53 gene at codon 72 has been described generating two biologically distinguishable variants, the P72 and the R72 variant, both critical to the cellular response to UV damage response. Addressing the still unresolved question of their respective implications in skin carcinogenesis is out of the scope of this communication, nonetheless it is interesting to note that the almost even prevalence of the Arg/Arg and Pro/Arg genotypes and the absence of the Pro/Pro genotype in our cases agrees with the data already reported for European populations [31] suggesting that, as far as the codon 72 is concerned, our series of patients do not represent a peculiar subset of population. Regarding the UV signature at specific hotspots in exon 7, the ARMS-PCR did not yield conclusive results while direct sequencing revealed a high number of point mutation, none of which however consisted in the canonical TT>CC or CT > CC transversion [1], suggesting that perhaps this kind of mutations, although specific, are comparatively infrequent in late lesions.…”
Section: Discussionsupporting
confidence: 87%
“…A dimorphism of the TP53 gene at codon 72 has been described generating two biologically distinguishable variants, the P72 and the R72 variant, both critical to the cellular response to UV damage response. Addressing the still unresolved question of their respective implications in skin carcinogenesis is out of the scope of this communication, nonetheless it is interesting to note that the almost even prevalence of the Arg/Arg and Pro/Arg genotypes and the absence of the Pro/Pro genotype in our cases agrees with the data already reported for European populations [31] suggesting that, as far as the codon 72 is concerned, our series of patients do not represent a peculiar subset of population. Regarding the UV signature at specific hotspots in exon 7, the ARMS-PCR did not yield conclusive results while direct sequencing revealed a high number of point mutation, none of which however consisted in the canonical TT>CC or CT > CC transversion [1], suggesting that perhaps this kind of mutations, although specific, are comparatively infrequent in late lesions.…”
Section: Discussionsupporting
confidence: 87%
“…Apparently, the expectations that lower capacity for DnA repair was always detrimental in terms of outcome were not met. What is more, it has been repeatedly demonstrated that the carriers of the R variant of the P72R polymorphism and especially the RR homozygotes were overrepresented (not underrepresented, as could be expected) in study groups with hPV-associated tumours (cervical carcinoma, Scchn) compared with the normal population, regardless of the smoking status (the latter being regarded as a major environmental risk factor for HPV-related carcinogenesis) (7,18,21). The finding of higher percentage of RR homozygotes, however, was found to be correct for true carcinoma only and not for precancerous highgrade cin (37).…”
Section: Hpv Hasmentioning
confidence: 75%
“…The low frequency p53 Arginine allele in the present study (10.3% for cases and 6.5% for controls) could be explained by the fact that frequency of p53 codon 72 Arginine allele increases with geographic distance from the equator and that fair skin population have higher frequency of p53 Arg allele than dark skin population. [21,22] Most of these studies were conducted on Caucasian population and only one involves Asian population in Iran 8 which included the BCC and revealed no significant difference in the p53 genotypes between patients and controls but indicated an increase in the frequency of arginine allele among sun exposed compared to control which may affect the risk of UV induced BCC. However, a positive association of the p53 codon 72 and BCC was found in transplant patient by McGregor, et al [1] but not in immunocompetent group.…”
Section: Discussionmentioning
confidence: 99%